PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA MELALUI KEPUASAN KERJA GURU SMA TUNAS LUHUR PAITON KABUPATEN PROBOLINGGO - Hartono, Muhammad Rudi (Jurnal Manajerial Bisnis, 2024)
This study investigates the relationship of four different variables, namely X1 (independent variable) principal's leadership style, X2 (independent variable) organizational culture, Y (dependent variable) teacher performance, and Z (intervening variable) job satisfaction. The data in this study were collected through an online survey using a Likert scale to teachers at SMA Tunas Luhur, Paiton, Probolinggo. Data analysis was performed using multiple regression methods (multiple regression). The data showcased that: 1) Leadership style and organizational culture have no significant effect on teacher job satisfaction; 2) Leadership style has a negative and insignificant effect on the Job Satisfaction variable; 3) leadership style and organizational culture through job satisfaction on teacher performance have a significant effect on teacher performance; 4) Job satisfaction has a positive and significant effect on variable Y (Teacher Performance). In conclusion, leadership style and organizational culture had no significant effect on teacher job satisfaction, leadership style and organizational culture through job satisfaction had a significant effect on teacher performance, and job satisfaction had a positive and significant effect on teacher performance. Moreover, the researchers suggest that future studies should reduce the number of statements on the questionnaire to minimize feelings of reluctance, fatigue, and origin in filling out the questionnaire. Then the statements in the questionnaire should be mixed between Favourable Statements and Unfavourable Statements to avoid the tendency for stereotypes to increase. In addition, future researchers should also confirm the research implementation schedule when collecting data so that respondents can be more focused when filling out the questionnaire.